Introduction - Simplice Asongu (African Governance and Development Institute (AGDI), 2018)
Sustainable development within the investigated context includes the ability of African countries to meet the present economic, social and environmental needs without compromising the ability of future generations to meet their own needs. A challenging contemporary policy syndrome is the lack of funding for adequate capacities and structures essential for the realisation of the post-2015 development agenda. This introductory chapter provides highlights on all chapters covered by the book in the direction of addressing the underlying policy syndrome.
Keywords: B17; B20; F35; F50; O10; 330; finance; sustainable development; Africa